Epistaxis as The Initial Presentation of Primary Sjögren Syndrome: A Case Report - Stephani Linggawan; Eric Satrio Adi Prabowo; Catherine Keiko Gunawan; Budiono Raharjo; Anton Sumarpo (Universitas Wijaya Kusuma Surabaya, 2025)
Background: Primary Sjögren syndrome is chronic systemic autoimmune disorder characterized by lymphocytic infiltration of the exocrine glands, most commonly presenting with dryness of the mouth and eyes. This case is very rare, which the antibody in the Sjogren's syndrome case concerns platelets. Objective: This case report emphasizes the occurrence of epistaxis in Sjögren Syndrome. Case Presentation: This case describes a 30-year-old male presenting with recurrent epistaxis as the initial clinical manifestation. Further clinical evaluation revealed hypertensive crisis and dryness in the mouth and nasal mucosa. The clinical presentation raised suspicion of an underlying autoimmune condition, prompting further testing, which confirmed the presence of anti -Sjögren’s syndrome type B (SSB) antibodies on an antinuclear antibody (ANA) profile. Result: The criteria for Sjogren's syndrome are based on the criteria if eye and mouth symptoms, eye and mouth clinical signs, and one of autoantibodies are found Anti-Ro (SSA), Anti-La (SSB), Antinuclear antibodies (ANA), Rheumatoid factor (RF). From this case has found symptoms of mouth and antibodies SSB. Conclusion: This case highlights that epistaxis can be caused by autoimmune cases, for epistaxis it is better to do screening for autoimmune examination test, emphasizing the need for further research to elucidate the diverse clinical manifestation, progression and prognosis factor.